Invitation for participation in a study - Johanna Weber (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
Participants needed for an international study on the impact of surrounding factors (family, job, training site, judges, ...) on sports performance. If you are interested, please check out the following link: https://www.umfrageonline.com/c/iycvfkqe